Explicit instruction of spoken requests: An examination of pre-departure instruction and the study abroad environment. (August 2017) - Halenko, Nicola; Jones, Christian
Abstract: The aim of this study is to evaluate the impact of explicit interventional treatment on developing pragmatic awareness and production of spoken requests in a study abroad context (taken here to mean those studying/using English for academic purposes in the UK) with Chinese learners of English at a British higher education institution. The study employed an experimental design over a 6 month period with 34 students assigned to either an explicitly instructed group or a control group receiving no instruction. Instruction took place prior to departure for the UK and performance was measured based on a pre-, immediate and delayed post-test design using an oral computer-animated production test (CAPT). The findings revealed that explicit instruction facilitated development of pragmatically appropriate request language in the short term and, to some extent, this was sustained over time. The CAPT data was also analysed in order to examine the use of internal and external modification of requests by each group. Results demonstrate that the explicit instruction group used significantly more modification at the immediate post-test stage but that the control group used significantly more at the delayed test stage. Highlights: Explicit instruction of spoken requests has a highly successful short term effect. Explicit instruction of spoken requests is not sustained in the long term. Instruction leads to significant increases in external and internal modification of request forms in the short term.